Demographic and genetic impacts of powdery mildew in a young oak (Quercus robur L.) cohort - Benoit Barrès; Cyril Dutech; Gilles Saint-Jean; Catherine Bodénès; Christian Burban; Virgil Fiévet; Camille Lepoittevin; Pauline Garnier-Géré; Marie-Laure Desprez-Loustau (Annals of Forest Science)
Abstract Key message By monitoring a field experiment over nine years, we investigated the impacts of the two main pathogen species Erysiphe quercicola S. Takam. and U. Braun and Erysiphe alphitoides (Griffon and Maubl.) U. Braun and S. Takam causing powdery mildew on a young cohort of pedunculate oak (Quercus robur L.), both from a demographic and genetic point of view using SNP markers. We show that survival rate is affected by mean disease severity. But while the growth-related tolerance to infection of the oak individual seems to be more determinant than resistance against infection, no equalizing effect of the disease could be detected. Context Studies on the effects of pathogens on the survival and population dynamics of forest trees are scarce. Yet a better understanding of these interactions could prove strategic in the challenging context of climate change. Aims Our general objective was to characterize the demographic and genetic impact of the two main pathogen species Erysiphe quercicola S. Takam. and U. Braun and Erysiphe alphitoides (Griffon and Maubl.) U. Braun and S. Takam causing powdery mildew in the early stages of a Quercus robur L. population. Methods An ad hoc field design with two disease exposures, natural and protected, was surveyed over nine years. This enabled a detailed phenotypic monitoring of 1733 emerging individuals from 15 progenies, and the genotyping of 68% of them. Results The pathogen induced high levels of seedling mortality several years after sowing, associated with reduced growth and capacity to overwinter. Fast-growing families showed the highest survival rate under both natural and protected disease exposure. Contrary to a possible trade-off hypothesis between growth and defense, family height potential was not negatively related to disease resistance across the studied oak mother trees. While supporting a deleterious effect of very low individual heterozygosity on the probability of survival, average genomic diversity was not significantly affected by mortality associated with powdery mildew. Our study also points to a few candidate genes for several fitness-related traits. Conclusion Overall, our results suggest that in oak natural populations, infection levels (related to resistance sensu stricto) may be less determinant than growth-related tolerance to infection for the fate of seedlings. However, an equalizing effect of powdery mildew on relative oak genotype performances cannot be excluded at later stages.